Algeria : 2005 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that the Algerian economy continues to benefit from abundant and increasing hydrocarbon revenues. Real GDP growth is expected to continue at about 5 percent in 2005, led by increased output in the hydrocarbon sector and sustained activity in the construction and services sectors. Executive Directors have welcomed the authorities' resolve to maintain fiscal sustainability over the medium term. They have stressed the importance of preparing comprehensive medium-term budget projections, and limiting increases in real wages to increases in productivity in the nonhydrocarbon sector.